OBJECTIVITY OF DESIGNING THE COMPUTERIZED ELECTRONIC PROGRAMMING TO DEVELOP A MODIFIED (KM-CBAS) SYSTEM TO DESCRIBE THE VARIOUS TEACHING BEHAVIORS ACCORDING TO THE DIRECT STYLE (COMMAND & PRACTICE) (Neo Scientific Peer Reviewed Journal, 2023)
The study also aimed at designing the computerized electronic programming to develop the (KM-CBAS) system to describe the various teaching behaviors according to the direct style of Moston and the researcher hypothesized that following There is a positive role of the computerized electronic programming developed from the (KM - CBAS) system in describing the various teaching behaviors according to the direct style of Moston. The researcher uses the descriptive curriculum with its analytical and comparative style. The study population was chosen from the teachers of physical education in Samarra / Salah al-Din Governorate for the academic year 2021-2022, they were (40) teachers whom were the actual workers and practitioners of the teaching profession, The study sample ,that was used for applying the trial on, was chosen from teachers (with experience) of physical education in secondary schools who had bachelor's degree, and who had actual teaching service for 10 years or more, and they were (NO: 7 17.5%). The research instrument was the observation system (KM-CBAS), then the researcher developed this system by converting it from the traditional form to electronic program that was controlled by the researcher using a computer. The system (KM-CBAS) and the statistical program (SPSS) were used for processing the data statistically. The researcher concluded that the objective organized observation using computerized electronic programming (KM-CBAS) is an effective tool for analyzing and describing the various teaching behaviors of experienced physical education teachers according to Moston's direct style. The researcher also recommends the use of computerized electronic programming (KM-CBAS), as it is an effective tool for analyzing and observing the various teaching behaviors and identifying them during teaching.